Metabolomic profiling, antioxidant activity, and skin cell viability of citrus peel flavonoids extracted via ultrasonic-assisted aqueous two-phase system - Shuiqing Lin; Jinmei Hu; Hui He; Yaying Yu; Zhengguo Zhou; Lin Zhou (PLoS ONE, 2025)
Citrus peels, often considered agricultural waste, are rich in flavonoids with potent antioxidant properties. This study utilized ultrasonic-assisted aqueous two-phase extraction (UA-ATPE) to obtain flavonoid-rich upper phase extracts (UPEs) from the peels of four citrus varieties sourced from different cultivars and regions. Targeted metabolomics was used to analyze the flavonoid compositions in the UPEs, revealing distinct metabolic profiles among the varieties. The antioxidant activities of the UPEs were evaluated through hydroxyl, superoxide, and ABTS radical scavenging assays, while their effects on skin cell viability were assessed using HaCaT and BJ cells. Multivariate statistical analyses, including principal component analysis (PCA) and hierarchical clustering analysis (HCA), identified six key differential metabolites (naringenin, p-coumaric acid, luteolin, butin, vitexin/isovitexin, and ferulic acid) that effectively distinguished the citrus varieties. Among the UPEs, Guangxi mandarin orange exhibited the highest total flavonoid content and the most potent superoxide anion and ABTS radical scavenging activities. However, Meizhou shatian pomelo demonstrated the strongest overall antioxidant capacity, as indicated by the lowest IC 50 values for the antioxidant potential composite (APC). Cell viability assays confirmed that none of the UPEs exhibited cytotoxicity at concentrations of 0.06--1.00% (v/v). These findings highlight significant varietal differences in flavonoid content and antioxidant activity, providing a scientific basis for the utilization of citrus peels in functional cosmetics and other industries.